Peran Green Marketing Dan Kualitas Green Product Terhadap Loyalitas Konsumen Produk Le Minerale: Analisis Mediasi Brand Trust Di Kota Batu - Irawati, Khusnul; Alrasyid, Harun; Arsyianto, Muhammad Tody (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This research seeks to examine the impact of green marketing and green product quality on consumer loyalty to Le Minerale products in Batu City, with brand trust serving as a mediating factor. Along with increasing consumer awareness of environmentally friendly products, companies need to implement sustainable marketing strategies that not only increase brand trust but also maintain customer loyalty. This research employs a quantitative approach using the Partial Least Square (PLS-SEM) method to analyze the relationships between variables. The results showed that green marketing and green product quality have a significant effect on brand trust, which then acts as a mediating variable in increasing consumer loyalty. These findings provide insights for companies in designing sustainability-based marketing strategies to strengthen competitiveness in the mineral water market in Indonesia. Keywords : Green Marketing, Kualitas Green Product, Brand Trust, Loyalitas Konsumen